ANTI-INFLAMMATORY AND PREBIOTIC POTENTIAL OF AGARICUS BISPORUS POLYSACCHARIDES AND THEIR APPLICATION IN SYNBIOTIC ALGINATE MICROCAPSULES - MEERA C R; ALAINA LYNAN; AKSHAYA C S (The Bioscan, 2025)
Edible mushrooms are widely cultivated across the world and have been part of the human diet since ancient times due to their culinary and medicinal properties. Polysaccharides are reported to be the most potent mushroom-derived components with several health benefits. The present investigation was carried out to analyze the anti-inflammatory, prebiotic, and synbiotic potential of polysaccharides isolated from the fruiting bodies of A. bisporus. Polysaccharides (PS) from this mushroom were isolated by hot water extraction, ethanol precipitation, deproteinization, dialysis, and lyophilization. Anti-inflammatory activity was studied by Cyclooxygenase (COX) inhibition assay, and PS showed a significant reduction in COX expression by 55.05%, at a dose of 100μg/ml. Prebiotic potential was studied by probiotic growth stimulation study using Lactobacilli species isolated from curd sample. The isolated Lactobacilli were identified by microscopic, cultural, and biochemical analysis. PS promoted the growth of Lactobacilli in a dose-dependent manner when added to the culture media. The synbiotic potential was studied by incorporating the PS in Sodium alginate microcapsules along with Lactobacilli species, and the drug considerably increased the viability of probiotic species compared to Control group. The present investigation indicates that A. bisporus is a viable choice for developing nutraceuticals with anti-inflammatory, prebiotic, and symbiotic potential.